Materiais mesoposoros e suas membranas na remoção de corantes orgânicos provenientes da indústria textil - Dorst, Diane Damaris (Universidade Federal de São Carlos, 2018)
Industrialization has led to a considerable increase in the number of pollutants. The main industrial companies that generate organic pollutants are the textile industries, which consume a significant volume of water that is colored in the dyeing process due to the presence of dyes that are not fixed in the fiber. Tanneries also generate large amounts of effluents, with high amounts of toxic products such as chromium. Therefore, there is interest in developing an environmental risk mitigation remediation system. In this work, the mesoporous material MCM-41 of the M41S family, and the functionalized mesoporous material MCM-41-NH2, were synthesized, by the post-grafting method, as well as the preparation of mixed matrix membranes (MMMs). The adsorption capacities of mesoporous materials were evaluated in the removal of remazol red and bright blue remazol dyes, as well as the possibility of using the membranes produced in the struggle of these dyes. The mesopores were characterized by Fourier Transform Infrared Spectroscopy (FTIR); Solid Nuclear Magnetic Resonance of 13C and 29Si (NMR); chemical adsorption/desorption of nitrogen; Transmission Electron Microscopy (TEM); Small-Angle X-Ray Scattering (SAXS) and Thermogravimetric analysis (TGA). The adsorption quantification of the remazol red and bright blue remazol dye was performed by Ultraviolet-Visible Spectroscopy (UV-vis) taking into account the initial adsorption variables, pH, amount of adsorbent, time and functionalization together. The quantification of chromium adsorption (Cr III) was performed by Nuclear Magnetic Tesonance in the Time Domain (NMR-DT). Dye removal indicators using mesoporous materials have a higher efficiency for MCM-41-NH2 at low dye concentration, low pH and a high amount of adsorbent. It was more than 87% adsorption to the remazol red dye and more than 99% adsorption to the bright blue remazol dye. The previous results on the removal of Cr (III) using MCM-41-NH2 were shown to have more than 75% adsorption. The membranes of PEI and MMMs of PEI/MCM-41-NH2 were characterized by FTIR; TGA; Exploratory Scanning Calorimetry (DSC) and Scanning Electron Microscopy (SEM). Water Vapor Transport (WVT) and permeation properties were also analyzed. It has also been observed, that the membranes have a barrier characteristic for the dyes.
Mesoposor materials and their membranes in the removal of organic dyes from the textile industry
Keywords: Mesoporo; MCM-41; MCM-41-NH2; Corantes têxteis; Remazol; Cromo; Membrana de matriz mista; PEI; CIENCIAS EXATAS E DA TERRA::QUIMICA